Science in the City: Contesting the City Architect’s Office in Toronto - Hull, James (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2012)
The City of Toronto experienced a major dispute over the functions of the office of the City Architect in the years just before World War One. Running through the dispute was the issue of science in the City. Did the City need, in the administration of technicalities and the addressing of technical questions, persons with a greater degree of scientific competency—as distinct from more traditionally trained personnel? Rhetorically, the question too was posed of whether “science” or “politics” should guide technical questions in the city’s business. The outcomes included a reorganized office of the City Architect, a new City Architect with stronger academic and professional credentials, a solemn promise from City Council to avoid interfering in his work and a building code which caught up with new practices in reinforced concrete construction.